2013
DOI: 10.1111/ejss.12104
|View full text |Cite
|
Sign up to set email alerts
|

The role of non‐crystalline Fe in the increase of SOC after long‐term organic manure application to the red soil of southern China

Abstract: Because of the important role of soil organic carbon (SOC) in nutrient cycling and global climate changes, there has been an interest in understanding how different fertilizer practices affect the SOC preservation and promotion. The results from this study showed that long-term application of manure (21 years) could increase significantly the content of SOC, total nitrogen (N) and soil pH in the red soil of southern China. The chemical structure of SOC was characterized by using solid-state cross-polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…The increase in total SOC content resulted from direct C input from the organic fertilizers and indirect C input from the increased net primary production as indicated by the increased grain yields through organic fertilization (Wen et al, 2014). This is consistent with the findings that organic fertilization could significantly promote soil C sequestration and thus contributed to long-term soil fertility improvement Zhang et al, 2013;Zhou et al, 2009). In the present study, the significant (P < 0.001) positive correlation between Feo and SOC indicated that Feo may play an essential role in the sequestration of C in this typical rice-wheat rotation paddy soil.…”
Section: Discussion Carbon Storagesupporting
confidence: 86%
See 3 more Smart Citations
“…The increase in total SOC content resulted from direct C input from the organic fertilizers and indirect C input from the increased net primary production as indicated by the increased grain yields through organic fertilization (Wen et al, 2014). This is consistent with the findings that organic fertilization could significantly promote soil C sequestration and thus contributed to long-term soil fertility improvement Zhang et al, 2013;Zhou et al, 2009). In the present study, the significant (P < 0.001) positive correlation between Feo and SOC indicated that Feo may play an essential role in the sequestration of C in this typical rice-wheat rotation paddy soil.…”
Section: Discussion Carbon Storagesupporting
confidence: 86%
“…9a), indicating that Feo could moderate the decomposition of SOC. This is consistent with findings of Zhang et al (2013), who reported that highly reactive non-crystalline Fe nanoparticles played an important role in the accumulation of SOC with a low alkyl C/O-alkyl C ratio after the long-term application of organic manure in the red soil of southern China. Furthermore, the positive correlation between Feo and the intensity of O-alkyl C (R 2 = 0.493, P = 0.004) may favor the accumulation of labile organic compounds in paddy soils (Eusterhues et al, 2011;Lalonde et al, 2012;Schwertmann et al, 2005).…”
Section: Effect Of Feo On Soil Organic Carbon Chemical Structuresupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that organic fertilisation increased the concentration of highly reactive Al and Fe minerals, which are strongly linked to the SOM preservation capability (Kögel-Knabner et al, 2008;Solomon et al, 2012;Yu et al, 2012;Zhang et al, 2013b;Vogel et al, 2014b). In this study, the soil sample from the MNPK-treated plot was rich in SOC (13.50 g/kg) and SON (1.70 g/kg).…”
Section: Direct Evidence Regarding the Preservation Of Som By Highly mentioning
confidence: 94%